POTENSI DAN PERMUDAAN TEGAKAN ALAM EBONI (Diospyros celebica Bakh.) DI AREAL HPH PT. INHUTANI I MAMUJU - Muh. Restu (PERENNIAL, 2006)
The intensive use of Eboni has caused a decrease of its natural population which has also contributed to the future loss of genetic potencies. Preservation efforts could only be conducted if the actual potencies of the stand and its environmental conditions were recognized. A study on stand and regeneration potencies as well as its soil characteristics is needed as a basic in management aplication for the increase of genetic potencies. This study used a systematic sampling survey method and laboratory analysis. The study aims to identify tree potencies and regeneration of Eboni Makassar as well as its soil characteristics under the stand. The results are expected to provide a description on Eboni Makassar potencies and its management efforts. It was found from the study that the potency of Eboni was 5.013 m3/ha with minimum and maximum estimated volumes of 3.163 m3/ha and 6.863 m3/ha, respectively. Eboni was naturally regenerated better in >40% slope category. Keywords: Eboni, Potencies and Regeneration, Various Slope